Disability, geographic and socioeconomic inequalities in access to insecticide-treated nets, and malaria prophylaxis among women in Uganda: A repeated cross-sectional study - Fredinah Namatovu; Vincent Rusanganwa (Journal of Community Systems for Health, 2026)
Introduction: Although Uganda has made substantial progress in malaria prevention and control, it remains unclear whether these interventions have equitably reached all subpopulations. This study aimed to assess disability, geographic, and socioeconomic disparities in access to insecticide‑treated nets (ITN) and Fansidar prophylaxis among women in Uganda. Methods: This repeated cross-sectional study analyzed Uganda Demographic and Health Survey data from women aged 15–49 years. Data from 2006 and 2016 were used in this study as they mark the first and most recent years with available disability data, respectively. Three outcome variables were included: 1) lack of ITN ownership, defined as “yes” if the household had no ITNs and “no” if it had at least one; 2) lack of ITN use, coded “yes” if a woman did not sleep under an ITN the night before the survey and “no” if otherwise; and (3) lack of Fansidar prophylaxis uptake, considered “yes” if the participant did not take Fansidar during her last pregnancy and “no” if she did. The absolute risk differences (ARD) and the slope index of inequality (SII) were calculated for each survey period. An interaction term between the independent variables and the survey period was included to assess changes in access to malaria prevention measures, and all models were adjusted for age. Results: Between 2006 and 2016, the prevalence of lack of ITN ownership declined from 64.1% to 39.5%, lack of ITN use from 77.9% to 23.6%, and lack of Fansidar prophylaxis uptake from 77.9% to 35.1%. Inequalities in the lack of ITN ownership decreased significantly by education, wealth and place of residence, but not by disability. Similarly, for lack of ITN use, geographic and socio-economic inequalities declined during the two time points, while disability-related inequalities persisted. For lack of Fansidar prophylaxis uptake, inequalities decreased across all stratifiers; however, the reduction was statistically significant only for education and wealth. Conclusions: Our findings suggest improvements in lack of ITN ownership and lack of ITN use as well as in lack of uptake of Fansidar prophylaxis. While geographic and socioeconomic inequalities decreased, disability-related inequalities persisted suggesting uneven progress. Policymakers should address the widening disparities between women with disabilities and those without and continue prioritising all underserved groups.